Design of capacitive MEMS transverse-comb accelerometers with test hardware (Superficies y Vacío, 2013)
This paper proposes the design of MEMS accelerometers, which include hardware to perform testing in a relatively simple way, with different manufacturing processes, PolyMUMPs™ and SUMMiT V™ of MEMSCAP and Sandia Labs respectively, using a methodology that allows them to be adapted to any of these technologies. This method was created to provide the basis to the designing of micro electromechanical devices, optimizing the learning time. The sensors are oneaxis transversal comb accelerometers which use an interdigital capacitors array to measure the capacitance change among three independent comb arrays when the system is exposed to positive or negative G forces. In addition, it includes another set of combs which interact as test devices, due to the fact that a voltage can be applied, which will create an electric field in the electrodes of these combs, producing an attraction force that will shift the mobile mass of the sensor, emulating an acceleration to which the device is exposed.Some physical parameters and dimensions proposed for this accelerometer are presented to show the design methodology of such devices. The accelerometers were designed under constraints set by the manufacturing regulations of PolyMUMPS and SUMMiT V™ The accelerometer layouts were designed using MEMS PRO v4.0™ and AutoCAD® and both were simulated with ANSYS Workbench®.